"Drugs are a taboo": a qualitative and retrospective study on the role of education and harm reduction strategies associated with the use of psychoactive substances under the age of 18 - Gabriela Almeida Pinto da Silva; Catarina Pinto Pereira; Marta Sofia de Sousa Pinto (BMC, 2021)
Abstract Background The use of psychoactive substances frequently starts at a younger age than adulthood. Considering the perspective of young people, this retrospective study tried to provide them with a role in identifying their own needs regarding drug use and interventions focused on it; the obstacles in accessing both general health and harm reduction services; the changes needed for a more effective, congruent and empowering response to the use of psychoactive substances before the age of 18. Methods The study was divided into two parts having both parts a qualitative focus. In the first part of the study, an online questionnaire was sent to all harm reduction teams and two focus groups were carried out with eight harm reduction professionals and six people who use(d) drugs. The second part used an online questionnaire applied to 143 participants aged between the age of 18 and 25 complemented by two semi-structured interviews. Results The need for education about psychoactive substances, namely in the educational context; the lack of information about available services; and the need for confidentiality were the most mentioned issues by the young people. Also, the informal network played a significant role in the participants relationship with psychoactive substances. Conclusions The lack of information was the most highlighted obstacle. Also, there is a confluence of various vulnerabilities such as being under 18, using drugs and the different social situations that they live in. To improve policy and practice regarding drug use among young people, harm reduction interventions must be scaled-up as well as intentionally driven to empower youth to deal with. School environment was chosen by participants as one of the elected environments to implement harm reduction services.